Alienation and dissent in the poetry of Allen Ginsberg and Fadhil Al-Azzawi - Geninah, Farah (AUC Knowledge Fountain, 2020)
This study explores the thematic similarities and contrasts between Allen Ginsberg’s Howl and Fadhil Al-Azzawi’s “The Teachings of F. Al-Azzawi.” To contextualize my topic, I briefly introduce the Beat generation as a whole, drawing parallels between them and the corresponding Kirkuk group in Iraq. Ginsberg and Al-Azzawi are, by and large, among the main spokespeople for said literary and cultural groups. The two groups were made up of marginalized individuals who struggled to fit in within mainstream society due to their controversial beliefs and lifestyles. I examine the prominent themes of alienation and dissent in the poems, and explore how these are manifested to reveal a better understanding of the speakers, their conscience and their contexts, all the while maintaining a distinction between the speaker and the poet. The speakers experience alienation in different forms: self-alienation, communal alienation and a sense of distancing from the nation. Moreover, they are both dedicated to dissent. They speak truth to power without necessarily ever taking a single political or ideological stance. The speaker in Howl details his generation’s unorthodox anecdotes and strongly criticizes the system which suppresses and ostracizes them. He points out the hypocrisy of a nation which deems his generation immoral for their alternative lifestyles when the system itself is the source of immorality in the poem. In “The Teachings of F. Al-Azzawi,” the speaker also seeks refuge amongst other marginalized individuals, while simultaneously struggling to define himself and his relationship with his nation. In Al-Azzawi’s poem “Elegy for the Living,” he directly confronts Ginsberg for not standing up against the US foreign policy towards Iraq. I particularly concentrate on the points at which the postcolonial and postmodern meet, with a strong emphasis on common features such as the poets’ confrontational, bold manner, the decentralization and deconstruction of various concepts, as well as the satirical tone which they adopt in their writing.